THE EFFECT OF HIBISCUS SABDARIFFA LINN ON TRABECULAR BONE MICROARCHITECTURE IN AN AGING MODEL DUE TO D-GALACTOSE INDUCTION: A HISTOMORPHOMETRIC STUDY - Fransiscus Asisi Alfareza; Neng Tine Kartinah; Trinovita Andraini; Imelda Rosalyn Sianipar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The aging process can cause an imbalance in bone remodeling and changes in trabecular bone microarchitecture. D-galactose induction is used as an experimental aging model because it can increase oxidative stress, while Hibiscus sabdariffa Linn. contains antioxidant compounds that have the potential to provide a protective effect on bone tissue. This study aims to analyze changes in trabecular bone microarchitecture in aging models due to D-galactose induction and the effect of Hibiscus sabdariffa Linn. This experimental study involved 22 samples divided into young normal (NM; n = 6), old normal (NA; n = 4), aging due to D-galactose induction (AA; n = 6), and aging due to D-galactose induction given by Hibiscus sabdariffa Linn. (AH; n = 6). Femur bone tissue was fixed, decalcified using formic acid, processed into paraffin blocks, and stained with hematoxylin-eosin. Trabecular bone images were taken in five fields of view using a 20× objective lens. Histomorphometric examination was performed to assess trabecular thickness (Tb.Th) and bone volume per tissue volume (BV/TV). Data met the assumptions of normality and homogeneity so they were analyzed using one-way analysis of variance followed by Tukey's post hoc test if there were significant differences. The significance level was set at p < 0.05. The mean Tb.Th in the NM, NA, AA, and AH groups were 71.61 ± 15.90 µm; 130.98 ± 11.31 µm; 120.61 ± 37.79 µm; and 100.48 ± 20.92 µm, respectively. There was a significant difference in Tb.Th values between groups with F (3,18) = 5.975 and p = 0.005. Post hoc test showed a significant difference between the NM and NA groups (p = 0.008) and between the NM and AA groups (p = 0.014). There was no significant difference between the AA and AH groups (p = 0.509). The mean BV/TV in the NM, NA, AA, and AH groups were 55.06 ± 11.06%, respectively.